DIGITAL INNOVATIONS IN THE LANGUAGE AND LITERATURE SPHERE: PROSPECTS FOR THE DEVELOPMENT AND ANALYSIS OF KEY ASPECTS OF THEIR APPLICATION - Лукіянчук, Інна (SWorldJournal, 2024)
The article explores the application of digital innovations in the field of language and literature, as well as their development prospects. The relevance of implementing alternative educational resources in the organization of the learning process is ju